Morphological and Biological Parameters of the Knapweed Nematode, Subanguina picridis - Watson, A K (Journal of nematology, 1986)
Specimens of the knapweed nematode Subanguina picridis (Kirjanova) Brzeski obtained from different host plants were highly variable in measurement and structure. This variability refutes the validity of six Subanguina species attacking plants in the Asteraceae